ショウワ キチ カンリ トウ ノ ケンセツ (2)カンリ トウ シザイ ノ コクナイ セイサク ト ショウワ キチ デノ ケンセツ - 半貫, 敏夫; ハンヌキ, トシオ; 佐野, 雅史; サノ, マサシ; 平山, 善吉; ヒラヤマ, ゼンキチ; Hannuki, Toshio; Sano, Masashi; Hirayama, Zenkichi (1993)
P(論文) 本論は管理棟資材の製作, 輸送及び昭和基地での建設など, 実施設計以降の製作過程についてまとめたものである。管理棟の建設工事は3年に分けて行われた。初年度の1991年1月には基礎工事と床面積138m^2の1階鉄骨構造部分の建設を行い, 1992年1月の第2年度工事では前年に完成した第1層躯体の上に2,3階の木構造部分合計583m^2を組み立てて建築本体を完成した。そして第3年度の1993年1月に給排水, 電気, 空調の各設備工事およびスプリンクラー, 煙感知器取り付けなどの防災設備工事を行って延べ床面積721m^2の大規模複合建築が昭和基地にできあがった。建築工事に要した日数は第3年度の設備工事を除く2期合計で94日, 実労働時間を1人1日7時間として合計2100人・日を費やした大工事であった。管理棟の建築で試みた新しい建築システムはまだ改良すべき点も多いが, コンクリート工事の省力化, 大断面集成材を用いた木構造の防火設計, 部品の大型化, 新接合法の考案など, 新しいプレファブ工法の可能性が示された。南極観測隊では建設担当者が毎年入れ替わるので多年度にまたがる工事では, 情報伝達のシステム化が望まれる。 Production, packaging and transportation of building elements of the new central building at Syowa Station are reviewed. Construction work of the new central building at Syowa Station is described. Construction of the central building was divided over two successive summer seasons. Foundation and steel frame work were executed in January 1991,and laminated timber structure work, exterior and interior finish work were done in January 1992. Electric, air conditioning and fire protection equipment and the plumbing system of the central building were set up in January 1993,to complete the new central building of Syowa Station with total floor area of 721m^2 and 3 stories. The building work required a large number of workingmen, 2100 in total. Each person worked 7-hours per day. This was the greatest construction project ever at Syowa Station. A new construction system with large scale laminated timber was used. The method of working with concrete in Antarctica was improved. A fireproof laminated timber structure was adopted. Large building elements and a new joint system of wooden elements were used in the construction. When construction work extends over two or more summer seasons, an appropriate system for giving information to the next construction party is needed because the construction workers of the Japanese Antarctic Research Expedition are changed every year. departmental bulletin paper